Karakteristik Saus Jeroan Cumi-Cumi dengan Penambahan Karagenan Sebagai Stabilizer - Chindya Lucky Pratiwi; Susi Lestari; Indah Widiastuti (Jurnal FishtecH, 2021)
Utilization of squid (Loligo sp) viscera waste with high levels of production and consumption of squid in the community. This study aims to determine the characteristics of squid (Loligo sp) viscera sauce with the addition of carrageenan as a stabilizer. This study used a randomized block design for parametric statistical data analysis and Kruskal-wallis method for non-parametric statistical data analysis. In this experiment, there were 4 treatments with 3 replications. The parameters used consisted of chemical parameters (moisture content, ash content, protein content, and carbohydrate content), physical analysis (viscosity and total dissolved solids) and sensory analysis (appearance, aroma, taste and consistency). The results showed that the squid viscera sauce with the addition of carrageenan had a significant effect on moisture content, ash content, protein content, carbohydrate content, viscosity and total dissolved solids. The sensory analysis results showed that the treatment had a significant effect on the appearance and consistency values, but had no significant effect on smell and taste values of the resulting squid viscera sauce.